Synthesis, Characterizations and Antimicrobial Activity of Cuprous Oxide (Cu2O) Nanoparticles - Regmi, Amrit; Bhandari, Janak; Bhattarai, Sitaram; Gautam, Surendra K. (Journal of Nepal Chemical Society, 2019)
Cuprous oxide nanoparticles were synthesized by the reduction of copper sulphate pentahydrate salt at different concentration using sodium borohydride as a reducing agent, polyethylene glycol-6000 as a stabilizer by simple, chemical co-precipitation methods and the effect of concentration on particle size were also studied. The crystalline size and phase of Cu2O nanoparticles (NPs) were authenticated by X-ray diffraction (XRD), morphology and structure by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and elemental analysis was carried out by energy-dispersive X-ray spectroscopy (EDX). The concentration-dependent antimicrobial properties of Cu2O NPs were studied for a different strain of bacteria. XRD and selected area electron diffraction studies (SAED) patterns confirmed the formation of face-centered-cubic Cu2O nanoparticles with size 4.77 nm and 8.02 nm at two different concentrations of 0.01 M and 0.1 M CuSO4, respectively. SEM and TEM images showed that the nanoparticles were uniform, in the form of clusters, and homogeneously distributed. EDX confirmed that synthesized nanoparticles were in pure form having copper and oxygen ratio 3:1 based on the atomic percentage of the chemical species. Cu2O nanoparticles showed excellent antibacterial activity against both bacterial strains Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli). The antibacterial activities of Cu2O NPs were found to be concentration-dependents and large bactericidal effect were seen for Gram-positive (Staphylococcus aureus) bacteria at higher concentrations of Cu2O NPs.